2020
DOI: 10.1002/adom.202000893
|View full text |Cite
|
Sign up to set email alerts
|

Highly Uniform, Self‐Assembled AlGaN Nanowires for Self‐Powered Solar‐Blind Photodetector with Fast‐Response Speed and High Responsivity

Abstract: Searching for power‐independent, compact, and highly environment‐sensitive photodetectors is a critical step towards the realization of next‐generation energy‐efficient and sustainable integrated optoelectronic systems. Particularly, the deep ultraviolet (UV) band, which has large photon energy, is extremely suitable for environment monitoring and invisible light communication application. Herein, the demonstration of self‐powered deep UV solar‐blind photodetectors in a photoelectrochemical (PEC) cell configur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 52 publications
1
77
0
Order By: Relevance
“…Then the redox molecule is reduced again to reproduce hydroxide ions at the platinum electrode (e − + OH * → OH − ). [36] Linear sweep voltammetry (LSV) curves of TaSe 2 NCs in 0. The P ph is gradually increasing with the illumination intensity because P ph is directly proportional to the P ϴ , where ϴ is the parameter related to the recombination process of the carrier and P is the power intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Then the redox molecule is reduced again to reproduce hydroxide ions at the platinum electrode (e − + OH * → OH − ). [36] Linear sweep voltammetry (LSV) curves of TaSe 2 NCs in 0. The P ph is gradually increasing with the illumination intensity because P ph is directly proportional to the P ϴ , where ϴ is the parameter related to the recombination process of the carrier and P is the power intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Self-powered PD is an essential part of a photoelectric sensing and communication system, which can continuously work without additional power sources [11][12][13]. Due to the outstanding advantages of eco-friendly, low cost and simple fabrication processes, self-powered photoelectrochemical (PEC) PDs have attracted extensive attention [12,14,15]. In another aspect, transparent optoelectronic devices provide many novel functions and have the potential for many applications, such as wearable intelligent electronics, imaging device, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups recently demonstrated self‐powered heterojunction UV PDs. [ 22–24 ] Chen et al [ 25 ] reported a self‐powered PD based on NiO and a ferroelectric (FE) material (Pb 0.95 La 0.54 Ti 0.46 O 3 ) with a responsivity of 0.18 mA W −1 and a low dark current of 1.3 pA. The device performance enhancement was mainly due to the combined FE depolarization field and the built‐in field.…”
Section: Introductionmentioning
confidence: 99%